Are midwives ready to fight vaccine hesitancy? First results from an Italian cross-sectional study. (13th November 2019) - Massimi, A; Rosso, A; De Vito, C; Marzuillo, C; Baccolini, V; Pitini, E; Barbato, D; Villari, P
Abstract: Background: Pregnancy is widely recognized as a 'teachable moment' since attitudes and beliefs about childhood vaccines are not completely structured. Among healthcare workers (HCWs), midwives play a pivotal role in the maternal care pathway and should have a key role also in promoting opportunities of discussion and correct information about vaccinations. Methods: We conducted a cross-sectional survey to assess knowledge and attitudes of a sample of Italian midwives towards vaccinations. A questionnaire was designed ad hoc and sent electronically to midwives members of the professional register of Rome. Results: Preliminary results on data collected from 140 midwives (mean age 37.32, DS ± 11.61; mean years on the job: 11.94 DS ± 12.78) who completed the survey showed a heterogeneous level of knowledge: only 50% of the sample indicated the correct threshold of vaccination coverage for herd immunity, while safety of multiple shots and of the additives contained in vaccines was reported by 61% and 31% of respondents, respectively. Only 41% of midwives had identified the pertussis vaccine as one of the vaccinations recommended during pregnancy. Attitudes were generally positive: 84% of respondents recognized recommended vaccines as effective and 86% as one of the safest health interventions. However, vaccinations against MMR and Varicella were perceived as useful by 86% and 71% of the midwives, while 89% and 77%, respectively, would recommend them to parents (compared to 96% in case of hexavalent). Globally, 79% of respondents would agree with the introduction of mandatory vaccinations for HCWs in maternity wards. Conclusions: Midwives show some gaps in the knowledge on vaccinations. The final results of this study will be used to build specific and tailored training programs directed to midwives involved in pregnancy management. This may help them to transfer the correct vaccination information for the empowerment and the growth of vaccine literacy. Key messages: Pregnancy is a strategic teachable moment to influence attitudes regarding childhood vaccinations and healthcare professionals must be trained to be the vehicle of the most accurate information. Specific under- and post-graduate training courses on vaccinations directed to midwives are strongly needed to ensure good level of knowledge on this topic.